Understanding the Role of Processes in Shaping the Compatibility of Contemporary Architecture in Historical Urban Environments - Jeongyoon Choi (Buildings)
The compatibility of contemporary architecture with historic urban contexts presents a complex and often contentious challenge for many cities, which have traditionally focused on physical design elements. This study emphasizes the critical role of procedural frameworks in shaping harmonious historic urban landscapes. Through case studies from Seoul and Gimpo in South Korea, Tomioka in Japan, and Graz in Austria, this study highlights the importance of processes such as design reviews, stakeholder engagement, and public education in urban heritage management. These processes—encompassing regulatory frameworks and the active involvement of communities and heritage experts—are found to be crucial as physical design elements in determining the success of integrating new developments into historical environments. Moreover, they must be adaptive to and capable of addressing the dynamic nature of urban environments while safeguarding cultural heritage values. This study reveals that procedural approaches, when properly implemented, enable the successful integration of contemporary architecture within historic contexts, fostering sustainable urban conservation. This study contributes to the evolving discourse on urban heritage management by broadening the concept of compatibility beyond mere design considerations to include the essential role of processes in shaping historical urban environments.